2019
DOI: 10.1111/bju.14799
|View full text |Cite
|
Sign up to set email alerts
|

Genomic classifiers for treatment selection in newly diagnosed prostate cancer

Abstract: Objectives To review systematically the literature on genomic tests for prostate cancer (PCa) and to evaluate the current state of the evidence on their use in patients with newly diagnosed PCa. Methods We conducted a systematic review by searching PubMed, Embase, Cochrane Central and conference abstracts from the American Urological Association, published between 2010 and 2018. Studies evaluating Prolaris, Oncotype Dx and Decipher assays were assessed for inclusion by two authors. Studies were excluded if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Decision curve analysis has been postulated as the most informative metric for an incremental predictive benefit [ 100 ]. These results support the view that there is considerable potential for improvement of the current prognostic models based only on clinicopathological factors by including molecular RNA markers [ 17 , 18 , 19 , 20 , 21 ]. Recently, the NCCN Prostate Cancer Guideline Panel suggested that tissue-based tests like Decipher, OncoType, Dx Prostate, Prolaris, and ProMark could be considered for initial PCa risk assessment [ 101 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Decision curve analysis has been postulated as the most informative metric for an incremental predictive benefit [ 100 ]. These results support the view that there is considerable potential for improvement of the current prognostic models based only on clinicopathological factors by including molecular RNA markers [ 17 , 18 , 19 , 20 , 21 ]. Recently, the NCCN Prostate Cancer Guideline Panel suggested that tissue-based tests like Decipher, OncoType, Dx Prostate, Prolaris, and ProMark could be considered for initial PCa risk assessment [ 101 ].…”
Section: Discussionsupporting
confidence: 81%
“…Although all clinicopathological factors are, to some extent, associated with patient outcome, the prognostic accuracy of these nomograms is generally unsatisfactory [ 12 , 13 , 14 , 15 , 16 ]. In this context, prognostic molecular biomarkers could significantly improve the predictive accuracy of tools based only on clinicopathological factors [ 17 , 18 , 19 , 20 , 21 ]. We recently elaborated a five-microRNA signature that outperforms the BCR scoring systems mentioned above [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are among the first independent groups to compare these panels in patients with primarily intermediate‐risk prostate cancer using clinically relevant endpoints. While the genes in the studied panels were found to independently contribute to risk stratification, their performance here was modest compared to earlier publications 12,18–21 . However, it should be noted, that the studied cohort was extremely challenging, as it was selected based on similar baseline clinical characteristics in cases and controls.…”
Section: Discussionmentioning
confidence: 70%
“…The NCCN Prostate Cancer Guidelines Panel stated in their 2019 guidelines that these tests might be considered for an initial risk stratification, based on biopsy samples and RP specimens [99]. Other current reports support this view [27,28,29,30,100,101,102]. Yet, the particularly different prognostic outcome results obtained by a head-to-head comparison of three tests (namely Decipher, Prolaris, and Oncotype), obviously complicate the routine implementation of these tests [103].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most powerful predictive scoring systems, CAPRAS was found to lack sufficient prediction accuracy in two meta-analyses [25,26]. Therefore, it is hoped that new tissue-based molecular biomarkers could be potential candidates to improve the disease recurrence prediction [27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%